70 Peer-Reviewed Perspectives of Innovation Capability for Service Industry: A Theoretical Approach - Oluwakemi T. OREAGBA; Olaleke O. OGUNNAIKE; Oladele J. KEHINDE; Chikaodi ORANUSI (Communications of International Proceedings, 2021)
The accelerated growth of the service sector is increasing and dominating all countries around the world. But the business environment is becoming more competitive due to globalization, technology development, and changes in consumer taste, needs and demands. To stay ahead in the business environment, both researchers and practitioners are taking advantage of the main tool (i.e., innovation capability) in such environment. Thus, the capability to innovate is now seen as a major driver in every unit of an organization. With the diverse interpretation of innovation capability, an analysis of these definitions played a significant role in understanding innovation capability for service. This paper presents an extensive literature review of 70 definitions of innovation capability. This study established business offerings, business environment, benefits and organizational resources are the mapped definition that encompasses innovation capability. This will give a clearer understanding and meaning of innovation capability among researchers, and practitioners for the service industry.
Keywords: Innovation Capability; Service Industry